2008
DOI: 10.1167/iovs.07-1517
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Gene Polymorphisms in the Complement Factor H Gene Are Associated with Exudative Age-Related Macular Degeneration in Chinese

Abstract: The findings support prior evidence that the CFH gene is one of the AMD-associated genes. There is a different distribution pattern of CFH variants in the Chinese compared with other populations. Individual SNP and haplotype analyses revealed that the ancient alleles at the 5' end of CFH contribute to an increased susceptibility to exudative AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 37 publications
7
33
3
1
Order By: Relevance
“…In our study, we did not find an association between CFH genotype and better visual acuity response with the higher-risk TC or CC genotypes after the first 6 months. Previous studies demonstrated that the frequency of the risk allele rs1061170 is high in Caucasians but low in Chinese populations [21,22,23]. This may explain why the present study failed to find any association between this SNP and response to treatment.…”
Section: Discussioncontrasting
confidence: 58%
“…In our study, we did not find an association between CFH genotype and better visual acuity response with the higher-risk TC or CC genotypes after the first 6 months. Previous studies demonstrated that the frequency of the risk allele rs1061170 is high in Caucasians but low in Chinese populations [21,22,23]. This may explain why the present study failed to find any association between this SNP and response to treatment.…”
Section: Discussioncontrasting
confidence: 58%
“…Recently, large population studies and meta-analyses came to identify the CFH Y402H variant as a significant genetic risk factor in Asian AMD [20,90], although the susceptibility conferred by the Y402H variant may not translate across ethnic lines. However, other multiple CFH variants have been shown to be associated with AMD in Asians [89,91,92,93]. In particular, the CFH I62V variant was significantly associated with AMD (allelic OR = 1.85, 95% CI = 1.63-2.09) in a meta-analysis of Asian cohorts although no significant association of this SNP was established with AMD in Caucasian populations [91].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Multiple independent studies have been performed to assess the association between Y402H and AMD in Asian populations [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]; meanwhile, rs1410996 is another polymorphism in the CFH gene, having been substantially reported to be related with AMD risk in Asian populations as well [10,13,17,21,23,24,25,26], but the results are still contradictory and inclusive.…”
Section: Introductionmentioning
confidence: 99%